2018
DOI: 10.1016/j.euf.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Metastatic Prostate Cancer Treatment Switch Decisions: A Multi-institutional Survey

Abstract: In this report we analyse the results of a questionnaire evaluating tools for clinical decision-making completed by 118 prostate cancer specialists. We found that most physicians favour clinical progression over prostate-specific antigen or imaging, and that criteria established by the Prostate Cancer Working Group are not widely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…In the management of CRPC patients, adequate response to therapy is challenging as the traditional Response Evaluation Criteria in Solid Tumors [ 11 ] frequently cannot be applied. The presence or absence of CTCs has emerged as a powerful biomarker to assess prognosis and therapy response [ 1 5 ]. Although the CTC numbers measured are extremely low, several ring studies have been conducted and demonstrated the robustness of the test, though a certain level of operator bias cannot be completely eliminated [ 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the management of CRPC patients, adequate response to therapy is challenging as the traditional Response Evaluation Criteria in Solid Tumors [ 11 ] frequently cannot be applied. The presence or absence of CTCs has emerged as a powerful biomarker to assess prognosis and therapy response [ 1 5 ]. Although the CTC numbers measured are extremely low, several ring studies have been conducted and demonstrated the robustness of the test, though a certain level of operator bias cannot be completely eliminated [ 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the CTC numbers measured are extremely low, several ring studies have been conducted and demonstrated the robustness of the test, though a certain level of operator bias cannot be completely eliminated [ 12 15 ]. In the original studies conducted with the CellSearch system, patient groups were divided in those with less or more than 5 CTCs per 7.5 mL of blood and shown to have different clinical outcomes [ 1 5 ]. However, recently it was demonstrated that the actual number of CTCs -and not just a count above or below a selected cut-off value- is of importance in order to assess response to therapy [ 4 , 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cell analysis may play an important role as a 'liquid biopsy', which will allow physicians to follow changes of the systemic part of the disease over time, enabling adjustment of treatment and thus a promising new diagnostic tool for patients suffering from e.g., breast cancer (36). The majority of the procedures have, however, been hampered by the paucity of these cells recovered by the different approaches particularly those using magnetic bead enrichment after a fixation step (38), which impedes statistical analysis of the circulating tumor cells (39). Apart from mere quantitative analysis, current research on circulating tumor cells is focusing on the identification of novel diagnostic and therapeutic biomarkers expressed by these cells, such as B7-H3 and Ki-67 on tumor cells circulating in the blood, which allows for the determination of the aggressiveness of the residual tumor load, and can thus contribute to the determination of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is common practice to change mCRPC treatment if there are signs of progressive disease, and in EXTREQOL 54% of patients had switched to next line therapies. According to a recent survey of 118 prostate cancer specialists, most clinicians favour clinical progression over prostate-specific antigen or imaging to drive treatment switch decisions [28]. Another recent survey of 109 specialists showed that treatment decisions are also influenced by whether or not patients live alone.…”
Section: Discussionmentioning
confidence: 99%